2019
DOI: 10.1371/journal.pone.0216484
|View full text |Cite
|
Sign up to set email alerts
|

Simulated optical performance of soft contact lenses on the eye

Abstract: Purpose To evaluate the impact of soft contact lens eye-fit on optical power by computational modelling and to produce correction maps for reversing this impact during the design process. Methods Finite element models of spherical and toric hydrogel contact lenses at varying nominal powers of -20 D to +20 D, base curves radii (R 1b ) of 8.2, 8.5, 8.8 mm, and overall diameters (d 3 ) of 14.5, 15.0, 15.5 mm were genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…The limitations associated with this study are the use of only three lens diameters and the fact that corneal geometry was kept constant throughout. The effect of corneal geometry on EPC has been demonstrated previously by Abass et al [23]. Upon consideration of their data, it was concluded that varying corneal geometry would display the same trends, except with a slight positive or negative shift in the EPC data.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The limitations associated with this study are the use of only three lens diameters and the fact that corneal geometry was kept constant throughout. The effect of corneal geometry on EPC has been demonstrated previously by Abass et al [23]. Upon consideration of their data, it was concluded that varying corneal geometry would display the same trends, except with a slight positive or negative shift in the EPC data.…”
Section: Discussionsupporting
confidence: 62%
“…The number of these elements used to model the eye and contact lens were 3280 and 2278, respectively. A mesh convergence study has demonstrated that this is the optimal number of elements to maximise accuracy whilst also not unnecessarily increasing computational time [23].…”
Section: Finite Element Modellingmentioning
confidence: 99%
“…each blink, which causes reaction of the lens in terms of its instantaneous deformation [29]. In addition to that, the eyelid exerts constant pressure on the cornea when the eye is closed.…”
Section: Plos Onementioning
confidence: 99%
“…This zone is substantial in contact lens fitting; it has been shown that the peripheral corneal shape has a more significant role in successful contact lens wear than the central radius of curvature of the cornea [3,4]. Also when a soft contact lens is fitted to a cornea, it is the peripheral zone that flexes and deforms most [5] which may then influence the optic zone, to which it is connected. Any deformation of the optic zone will, in turn, affect the optical power profile.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the EPC in soft contact lenses when worn on-eye, a few techniques have evolved in the literature [5]. Strachan et al [6] proposed a technique to demonstrate the effect of lens geometry on the power of the lens on-eye.…”
Section: Introductionmentioning
confidence: 99%